Active demultiplexing of single photons from a solid‐state source. Issue 3 (11th April 2017) - Lenzini, Francesco; Haylock, Ben; Loredo, Juan C.; Abrahão, Raphael A.; Zakaria, Nor A.; Kasture, Sachin; Sagnes, Isabelle; Lemaitre, Aristide; Phan, Hoang‐Phuong; Dao, Dzung Viet; Senellart, Pascale; Almeida, Marcelo P.; et al.
Abstract : Single photons from a solid state‐source are deterministically routed into different output modes by a fully integrated active optical switch network. This scheme creates a multi‐fold single‐photon source from a micro‐pillar quantum dot, providing a crucial resource for photonic quantum information applications. Abstract: A scheme for active temporal‐to‐spatial demultiplexing of single photons generated by a solid‐state source is introduced. The scheme scales quasi‐polynomially with photon number, providing a viable technological path for routing n photons in the one temporal stream from a single emitter to n different spatial modes. Active demultiplexing is demonstrated using a state‐of‐the‐art photon source—a quantum‐dot deterministically coupled to a micropillar cavity—and a custom‐built demultiplexer—a network of electro‐optically reconfigurable waveguides monolithically integrated in a lithium niobate chip. The measured demultiplexer performance can enable a six‐photon rate three orders of magnitude higher than the equivalent heralded SPDC source, providing a platform for intermediate quantum computation protocols.